HELEN'S STRUGGLE TO RAISE HER COUSINS IN GHARRY MARSHALL'S RAISING HELEN (2004): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - PRIHASTUTI, YUNITA (2011)
This problem statement of this study is how Helen's struggle to raise her cousins in Raising Helen. The object of the research is the movie entitled Raising Helen by Gharry Marshall. The researcher uses Alfred Adler of Individual Psychological theory. The study belongs to qualitative study in which the writer uses two data sources, namely primary data source and secondary data source. The primary data source is the movie Raising Helen it self, meanwhile the secondary data source are any books of literature and psychology related to this study. The writer collects the data from both primary and secondary data source in a sort of document evidence. From the result of analysis, it can be drawn some conclusion. Firstly, Gharry Marshall wants to utter his idea that struggle to be a good mom should be achieved by sacrifice, and struggle to be a good mom will influence the psychological development of the major character. In this movie, Helen Haris as the major character has to struggle to be a good mom for her cousins to reinforce her psychological development.